Strategies supporting the prevention and control of neglected tropical diseases during and beyond the COVID-19 pandemic - John P. Ehrenberg; Xiao-Nong Zhou; Gilberto Fontes; Eliana M. M. Rocha; Marcel Tanner; Jürg Utzinger (BMC, 2020)
Abstract Emerging and re-emerging zoonotic diseases represent a public health challenge of international concern. They include a large group of neglected tropical diseases (NTDs), many of which are of zoonotic nature. Coronavirus disease 2019 (COVID-19), another emerging zoonotic disease, has just increased the stakes exponentially. Most NTDs are subject to the impact of some of the very same human-related activities triggering other emerging and re-emerging diseases, including COVID-19, severe acute respiratory syndrome (SARS), bird flu and swine flu. It is conceivable that COVID-19 will exacerbate the NTDs, as it will divert much needed financial and human resources. There is considerable concern that recent progress achieved with control and elimination efforts will be reverted. Future potential strategies will need to reconsider the determinants of health in NTDs in order to galvanize efforts and come up with a comprehensive, well defined programme that will set the stage for an effective multi-sectorial approach. In this Commentary, we propose areas of potential synergies between the COVID-19 pandemic control efforts, other health and non-health sector initiatives and NTD control and elimination programmes.